The potential contribution of the Territorial Regulatory Plan to offset the disaster take place in the City of Upala, Province of Alajuela, Costa Rica, associated with the passage of Hurricane Otto - Barrantes-Castillo, Gustavo; Valverde-Calderón, José Francisco; Sandoval-Murillo, Luis; Romero-Romero, Arvin; López-López, Max; Vargas-Hernández, Annie (Revista Geográfica de América Central., 2021)
There has been speculation among public opinion television programs regarding the hypothetical benefits that the proposed Territorial Regulatory Plan of the canton of Upala, prepared by the School of Geographical Sciences of the Universidad Nacional, could have had if it had been approved a few years before the passage of Hurricane Otto. This article describes the scope that said plan had in terms of restricting land use in the then considered flood susceptible areas, but not before performing a historical environmental analysis of the relationship existing between the community of Upala and the Zapote River. Additionally, through the gathering of field evidence and the use of geographic information systems (GIS), it was possible to reconstruct reached water levels and relate flooding behavior to the city’s distribution and the forecasts made in the Territorial Regulatory Plan. Results indicate that the behavior of this extreme natural event was not foreseen thus causing a strong impact in areas previously zoned and approved for residential and governmental use. This experience invites to reflect on the need to consider climate change in territorial planning.